Animasi Interaktif Untuk Pembelajaran Matematika Dasar - Siti Kusnul Wulandari; Eka Rini Yulia (Universitas Bina Sarana Informatika, 2019)
Abstract - Adobe Flash CS4 is software that is widely used by web and graphic professionals because of its ability to support multimedia, a combination of graphics, animation, sound and interactivity for internet users. The interactive module application has the advantages of interesting facilities such as music, animation and quiz questions consisting of text. Researchers tried a little in the world of education by making interactive animations for basic mathematics learning. The researcher made this interactive animation in the hope that it could help this research be useful and useful in counting and memorizing numbers. This Interactive Module is also equipped with quiz questions so users can use their abilities. Keywords: Animation, Basic Mathematics Learning, Adobe Flash CS4